IMPLEMENTASI KEBIJAKAN DALAM PELAYANAN IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DI KOTA PEKANBARU TAHUN 2024 - Syuhada, Halfina; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
IKD aims to analyze the implementation of Digital Population Identity (IKD) service innovation in Pekanbaru City in 2023 - 2024. The formulation of the problem in this study is how to implement and what are the supporting and inhibiting factors for Digital Population Identity (IKD) service innovation in Pekanbaru City in 2023 - 2024. The purpose of the study was to determine the supporting and inhibiting factors for the implementation of Digital Population Identity (IKD) service innovation in Pekanbaru City. The type of research used in this study is field research. The theory used in this study is Edward III's Implementation theory. The results of the study are as follows: communication is carried out by implementing socialization carried out by the Population and Civil Registration Service. It is optimal. Resources can be seen by accessing the link or IKD service registration application. The disposition of reviewing public interest in this IKD service was well received. The bureaucratic structure is the process of implementing andong services is going well in accordance with the established SOP. The supporting factors for this success are mainly due to officers who are always ready to provide the best service to the community. The inhibiting factors usually come from the community who sometimes do not want to register for IKD. The local government, especially the Population and Civil Registration Service of Pekanbaru City, must be more active in directly socializing the existence of this IKD service, such as introducing the community to the importance of this digital identity through socialization at the Car Free Day event held in the center of Pekanbaru every Sunday. Recommendations for the results of this study are: The community should support the IKD service by registering their NIK to the digital identity so that the government's program to improve the security of identity use is successful. The central government should continue to innovate so that this IKD application can be used and supported by all smartphones that enter Indonesia as a default application. Keywords: Implementation, Innovation, IKD Services.